THE ANALYSIS OF STUDENTS’ LISTENING SKILL THROUGH LISTENING TO ENGLISH SONG - Annisa Tasyakurna M; Rahma Widi; Eggi Pratama (Sekolah Tinggi Keguruan dan Ilmu Pendidikan Darud Da'wah Wal Irsyad Pinrang, 2026)
This research aimed to analyze the students’ listening skill through listening to English song. This was descriptive quantitative research. The participants consisted of 15 undergraduate students of the first semester at Institut Az Zuhra. Test and Interviews were conducted to collect data. In data analysis, the text was given in the form of missing lyrics. The students were asked to listen to the music and identify any missing lyrics by the researcher. The music was played three times. Then, the researcher gathered the students’ response sheets. The researcher will take the following actions in order to analyze the data: First, the researcher examined the listening test results. Then the researcher counted the data. The last, researcher gave the score to the test. The result of the research found that the students’ listening skill through listening to English song was very good. There were seven students got very good score, five students got good score, two got enough score and one got less score It was fun, enjoyable, and interesting for the students. Listening to English songs not only makes them relax and enjoy but can also enrich their vocabulary and tell them how to pronounce a word in English.